2021
DOI: 10.3389/fnagi.2021.640188
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Show Reduced Spatial Precision but Preserved Strategy-Use During Spatial Navigation Involving Body-Based Cues

Abstract: Older adults typically perform worse on spatial navigation tasks, although whether this is due to degradation of memory or an impairment in using specific strategies has yet to be determined. An issue with some past studies is that older adults are tested on desktop-based virtual reality: a technology many report lacking familiarity with. Even when controlling for familiarity, these paradigms reduce the information-rich, three-dimensional experience of navigating to a simple two-dimensional task that utilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…The spatial reorientation deficit we observed could explain the cause of spatial disorientation which is one of the first symptoms in humans with AD (Coughlan et al, 2018). Further, spatial navigation tasks like the one employed here can easily be adapted for humans as has been done with a variety of spatial navigation learning and memory tasks (e.g., Puthusseryppady et al, 2020;Mcavan et al, 2021). Our approach for identifying these brain network profiles is unique.…”
Section: Discussionmentioning
confidence: 90%
“…The spatial reorientation deficit we observed could explain the cause of spatial disorientation which is one of the first symptoms in humans with AD (Coughlan et al, 2018). Further, spatial navigation tasks like the one employed here can easily be adapted for humans as has been done with a variety of spatial navigation learning and memory tasks (e.g., Puthusseryppady et al, 2020;Mcavan et al, 2021). Our approach for identifying these brain network profiles is unique.…”
Section: Discussionmentioning
confidence: 90%
“…The hippocampus, parahippocampal cortex, posterior cingulate cortex, prefrontal cortex, and parietal lobes are thought to have a significant impact on VSF, and are highly susceptible to the effects of ageing, manifesting as a decline in learning ability and executive functioning in older adults. Moreover, maintaining long-term memory and brain plasticity requires gene expression, which is known to decline as the body ages, which may also contribute to the decrease in motor functioning in older people [15]. Interestingly, most biophysical properties of neurons do not change during the ageing process.…”
Section: Discussionmentioning
confidence: 99%
“…Participants have to understand the flexible relationship between the cues available in the virtual environment to determine positions. Other studies compared spatial perspective-taking abilities in young and old adults, demonstrating that age is related with decay of these skills 17 , 72 . When testing recognition of positions, it was demonstrated that young adults also outperformed old adults 73 75 .…”
Section: Discussionmentioning
confidence: 99%
“…That is, the viewpoint the agents physically preserve is mentally reoriented into alignment with the to-be-adopted viewpoint. As a result, some studies reflect that linearly increasing angular disparities between the original and to-be-adopted perspective translate into more errors 5 , 17 . Also, better response times and accuracy are reported when the novel views of an environment are presented in alignment with previously encoded ones 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation